Women in Christianity in the age of Enlightenment - Córdova Quero, Hugo; Mor, Cristian (A cultural history of women in Christianity, 2026)
"This volume offers a multidisciplinary reassessment of women's intellectual, spiritual, and artistic contributions during the Enlightenment, challenging their place in dominant historical, theological, and philosophical narratives. Women in Christianity in the Age of Enlightenment brings together eight thematically interconnected chapters that examine how women across diverse geographies navigated patriarchal institutions to assert agency in theology, philosophy, sainthood, education, science, the arts, and religious practice. Drawing from a wide range of case studies, the volume traces counter-narratives that questioned Enlightenment rationalism, ecclesiastical authority, and canonical androcentrism. Featured figures include the Puellae Doctae, Rachel Speght, Jeanne Guyon, Mary Astell, and Élisabeth Vigée-Lebrun in Europe; "Mamá Antula," Sor Juana Inés de la Cruz, Francisca Josefa del Castillo, and María de Jesús in the Americas; and Luo Qilan, Kiyohara Yukinobu, and Ike Gyokuran in Asia. The volume reframes the Enlightenment as a contested global terrain of gendered power. This book will appeal to scholars and advanced students in gender studies, theology, intellectual history, and the arts, as well as to general readers interested in the Enlightenment and feminist thought. It offers a valuable resource for rethinking modernity through the often-overlooked contributions of women to Christian intellectual and cultural traditions worldwide"-- Provided by publisher